Performance evaluation and finite element modeling of heat, mass, and fluid flow inside a hybrid solar dryer during drying of paddy grains - Jha, Aprajeeta; Tripathy, P. P. (Frontiers in Food Science and Technology, 2024)
Introduction A comprehensive assessment of a photovoltaic (PV) integrated hybrid solar dryer (HSD) for drying paddy was undertaken in the present investigation. Performance evaluation of the system along with finite element model of HSD at no-load and load conditions were successfully developed. Methods A three-dimensional PV aided hybrid solar dryer assembly model was created in indoor simulations using COMSOL Multiphysics version 5.3 a. Solidworks 16 was used to build the dryer’s collector, drying chamber, chimney, and thin food grain layer.Mesh refinement tests verified the mesh size independence of the panel temperature forecast finite element model. Results and Discussion Collector efficiency ranged from 49.24% to 81.19% and peaked at 750 W/m2 thermal intensity. System evaporation ranged from 0.25 to 0.39 kg/h. We also compared HSD, tray dryer (TD), and mixed-mode solar dryer (MMSD) system efficiency, specific energy consumption (SEC), and specific moisture extraction rate (SMER). HSD SEC values were 72% and 46% lower than TD and MMSD. HSD, MMSD, and TD had SMER values of 0.27, 0.15, and 0.08 kg/kWh. HSD dried paddy samples 36.36% and 84.61% faster than TD and MMSD. Hybrid solar dryers saved 33% and 50% more time than mixed mode and tray dryers, respectively. Simulations of the collector and chamber air distribution profiles showed a dead zone where air velocity drops below 0.5 m/s. I must note that the model accurately predicted the dryer’s temperature, wetness, and air dispersion pattern at load and no-load. PV-assisted HSD is suitable for sustainable food grain drying, according to this study.